APPLICATION OF BARIUMSTRONTIUM CARBONATES FOR PROCESSING OF CREEP-RESISTING STEELS - A. P. Bezhok; S. P. Zadrutskij; S. V. Korneev; V. A. Rozum; I. A. Trusova; G. P. Goretskij (Литьë и металлургия)
The results of researches on influence of bariumstrontium carbonates on structure, mechanical and foundry properties of heat resisting chrome-nickel steels of austenitic type are given.